PENGGUNAAN METODE BELAJAR ROLE PLAYING TERHADAP AKTIFITAS BELAJAR ANAK SUB POKOK BAHASAN PENGENALAN HEWAN DARAT - Inna Hamida Zusfindhana (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
This research is motivated by the objective condition of children who have difficulty learning in knowing land animals. The method of learning role playing is one of the learning methods used to overcome it. The purpose of this study is to improve the learning activities of children of sub-subject of animal introduction. The method used in this research is qualitative method using observation and interview to dig the child data. The subjects of the study were children with intelectual disability aged 9 years amounted to one person. The results showed that: 1) The cognitive development of the child is still like 6 years old children, 2) The children need services that suit their needs through role playing learning method, 3) role playing method done six times, 4) role playing method can increase Learning activities of children in knowing land animals.